Inventory Management Strategy and Performance of Manufacturing Firms in Kenya - Awory, Oscar Barasa; Chege, Denis; Namusonge, Eric (International Journal of Supply Chain and Logistics, 2025)
Purpose: The main objective of this study was to establish the effect of inventory management strategy on the performance of manufacturing firms in Kenya. This study was guided by Stochastic Inventory Model. Methodology: Cross-sectional research design was adopted. The population of this study was 1032 manufacturing firms in Kenya from which a study sample of 288 respondents was selected using Yamane formula. The study used purposive sampling to select senior managers from production and Supply Chain management. Primary data was obtained from the respondents using a self-administered questionnaire. On the other hand, secondary data was obtained from relevant published records, journals, magazines, and newspapers among other public sources. Data analysis was conducted using descriptive and inferential analysis. Descriptive analysis was presented using means and standard deviation. Findings: The study findings revealed that inventory management strategy has a positive and significant influence on the performance of manufacturing firms in Kenya. The study concluded that inventory management strategy has a positive and significant influence on the performance of manufacturing firms in Kenya. Unique Contribution to Theory, Policy, and Practice: The study recommended that firms should focus on implementing effective inventory management strategies such as accurate demand forecasting, efficient inventory control, and optimized inventory levels. The study adds to theory by showing inventory management as a key driver of performance, informs policy by supporting guidelines for modern inventory systems, and guides practice by urging firms to adopt accurate forecasting and efficient control for improved competitiveness.